THE COLLEGE TEXTBOOK. A METHODOLOGICAL APPROACH - Reynosa Navarro, Enaidy (2016)
In this article, the reader will find methodological guidelines on how to write a college textbook. It offers procedures for setting up a work team responsible for the preparation of textbooks; explains how to define the topics to be addressed, as well as procedures for information management, and detection of appropriate literature. Additionally, it emphasizes theoretical research types, interpretation of theories, theoretical conclusions and the pedagogical function of the college textbook. Finally, it provides some editorial guidelines, such as textbook structure, notes, bibliographical references, images and charts, authors’ biographies, correction stage, and final review up to distribution.